Pengaruh Brand Image terhadap Positive Word-of-Mouth melalui Brand Love dan Brand Commitment pada Pengguna Tokopedia di DKI Jakarta - Pandhu Yuan Syuhada; Muwafick Hidayat (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study was to determine the effect of brand image on positive word-of-mouth through brand love and brand commitment to Tokopedia users in Jakarta. This research design uses descriptive research and causality research, measuring each variable using a 5-point Likert scale. This study uses primary data with data collection through questionnaires. The sampling used in this research is purposive sampling and obtained asample of 180 respondents. This study uses a statistical method with SMART PLS 3.2.9 as a test tool. The results of this study indicate that brand image has no effect on positive word-of-mouth on Tokopedia users in Jakarta, whilebrand image has an influence on brand love and brand commitment on Tokopedia users in Jakarta, then brand love and brand commitment have a positive influence. word-of-mouth to Tokopedia users in Jakarta.